Transformasi Perilaku Preventif Remaja: Integrasi Kebijakan dan Motivasi Internal sebagai Kunci Berkelanjutan - Zela, Nurma; Badri, Isna Aglusi; Putri, Yulia Devi; Febrina, Trisya Yona (Pustaka Galeri Mandiri, 2026)
Maintaining preventive health behaviors among adolescents remains a significant challenge in building a resilient society. Compliance driven solely by external regulations is often temporary and fragile. To achieve sustainable behavioral transformation, a deep understanding of how policy frameworks interact with adolescent internal motivation is required. This study aims to analyze the relationship between policy support and adolescent motivation in internalizing long-term preventive behaviors. A quantitative study with a cross-sectional design was conducted on 427 adolescents selected through purposive sampling. Data were collected using structured questionnaires and analyzed using Pearson correlation and linear regression tests to measure the strength of the relationship between variables. The analysis revealed a mean policy score of 17.90 and an adolescent motivation score of 39.50. A significant positive correlation was found between policy and adolescent motivation (p=0.001; r=0.431). These results indicate that inclusive and effective policies act as catalysts, enhancing adolescents' internal drive to independently comply with health standards. Public policy should no longer be viewed as an instrument of coercion, but rather as a supportive ecosystem that fosters internal motivation. Sustainable transformation of preventive behavior requires policy approaches that empower adolescents, rather than merely restricting them. Future health strategies must focus on integrating participatory policies with the strengthening of adolescent health autonomy, ensuring that preventive behavior becomes an ingrained aspect of their daily lives.